Screening of in-vitro Antidiabetic Potentials from the Protein Extracts of Stomopneustes variolaris - Bharathi , V. Ratna; Prabha , Y. Shanti (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Diabetes mellitus (DM) is one of the serious endocrine disorders caused by insufficient production or inefficacy of the insulin and it is the immense cause of death throughout the world. However, finding for novel antidiabetic drugs from natural resources is still fascinating, because of their safe effect on DM. The marine environment provides a pool of unique and novel bioactive compounds due to its extremely diverse environmental conditions and biota. Stomopneustes variolaris is a marine echinoderm, belongs to family Stomopneustidae and they have toxins in their bodies as a defence mechanism which often has medicinal value. The present investigation aimed to evaluate the antidiabetic potentials of protein extracts from the spines, shell, and tissue of Stomopneustes variolaris. The spine, shell, tissue shows significant variation in protein content and the highest concentration of protein was found in tissue extract. The studies of haemoglobin glycation reveal that the haemoglobin glycation was increased with increasing concentration of the glucose. The highest haemoglobin glycation was reported in 20mg/ml glucose concentration at 24hr incubation period. The Glucose Adsorption Capacity of spine, shell and tissue extracts shows a strong positive correlation such as r = 0.9930, r = 0.9931 and r = 0.9969 corresponding to increased glucose concentration. The inhibition percentage of physiological haemoglobin glycation was depended on the glucose concentration. The protein extract of Stomopneustes variolaris spine (86.19 ± 0.28) showed the highest percentage of physiological haemoglobin glycation inhibition at 40mg/ml glucose concentration. The % of Glucose dialysis retardation index (GDRI) was decreased with increasing time incubation in all the tested protein extracts. The spine extract of Stomopneustes variolaris (37.26 ± 0.4) showed the highest percentage of GDRI at 30min incubation period. The maximum percentage of glucose uptake by yeast was observed with the spine extract (46.4±0.25) of Stomopneustes variolaris. The in-vitro α-amylase inhibitory activities of Stomopneustes variolaris spine, shell, and tissue were found as 51.11±0.79%, 41.81±0.31% respectively.